THE HISTORY AND DEVELOPMENT OF PRIME NUMBERS - Muneer Ahmad Sofi; Sobiya Jan (PT. Radja Intercontinental Publishing, 2025)
Prime numbers have captivated mathematicians for centuries due to their foundational role in number theory and their extensive applications in fields such as cryptography, computer science, and pure mathematics. This paper traces the historical development of prime numbers, beginning with early explorations in ancient Greece and continuing through significant advancements in modern mathematics. Key contributions from renowned mathematicians such as Euclid, Euler, Gauss, and Riemann are discussed, as well as the impact of prime numbers on contemporary technologies, particularly in encryption and computational research. The evolution of prime number theory, including ongoing research on the Riemann Hypothesis, is explored to emphasize the ongoing relevance and mystery of primes in both mathematics and technology.